Empowering 21st Century Skills: The Impact of Independent Curriculum Modules on Elementary Students - Dafit, Febrina; Latif; Ain, Siti Quratul (Jurnal Ilmiah Sekolah Dasar, 2024)
This study was motivated by the problem of students' weak reading literacy and 4C skills in elementary schools. Reading literacy and 4C skills are essential components of 21st-century education that need to be developed through effective learning processes. The research aims to analyze the effect of the Independent Curriculum teaching modules on improving reading literacy and 4C skills among fourth-grade elementary students. A quantitative approach with an experimental design was employed in this study. The sample consisted of 148 fourth-grade students selected using a purposive sampling technique. Data collection techniques included tests to measure reading literacy and observation sheets to assess 4C skills. Instrument validity and reliability tests were conducted to ensure the quality of the research tools. Data analysis was performed using Multivariate Analysis of Variance (MANOVA) to test the research hypotheses. The results indicate that the Independent Curriculum teaching modules significantly influence the improvement of students' reading literacy and 4C skills. In conclusion, the implementation of the Independent Curriculum teaching modules enhances students' ability to comprehend texts and develop essential 21st-century skills needed to face future challenges.